Performance trends of an air-cooled steam condenser under windy conditions - Van Rooyen, J. A. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2007.